The Smell of Air Pollution: Olfactory Senses and the Odour of Canadian Oil, 1858-1885 - Armstrong, Robert (Ontario History)

(untitled) (The Ontario Historical Society, 2020)
Beginning in 1858, Enniskillen Ontario was the site of Canada’s first oil industry. Over the course of the next twenty-seven years, Canada’s oil industry struggled to sell Enniskillen oil because it possessed a pungent odour. Although using one’s olfactory senses is biological, how people choose to interpret odours is influenced by their cultural context. As a result, different populations reacted to the odour of Enniskillen oil based on their socioeconomic and geographic context. In Britain, people responded negatively to the smell of the oil, going so far as trying to ban the importation of oil from Canada. Across cities in Ontario, people raised complaints about the smell of the oil, but their concerns were largely ignored by municipal officials. In the oil region of Enniskillen, the locals were largely unbothered by the oil, despite living in a region that had been polluted to such an extent that the air was permeated with the smell of oil.